2016
DOI: 10.1007/s00404-016-4139-1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent shoulder dystocia: is it predictable?

Abstract: Shoulder dystocia is an independent risk factor for recurrent shoulder dystocia. Deliveries in women with a history of shoulder dystocia are characterized by higher rates of operative delivery, prolonged second stage of labor and macrosomia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Complications for the infant include brachial plexus injury and fractures, most commonly of the clavicle and humerus . It has been found that maternal factors including diabetes, multiparity, macrosomia and previous shoulder dystocia can increase the risk of shoulder dystocia …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications for the infant include brachial plexus injury and fractures, most commonly of the clavicle and humerus . It has been found that maternal factors including diabetes, multiparity, macrosomia and previous shoulder dystocia can increase the risk of shoulder dystocia …”
Section: Introductionmentioning
confidence: 99%
“…5 It has been found that maternal factors including diabetes, multiparity, macrosomia and previous shoulder dystocia can increase the risk of shoulder dystocia. 1,[7][8][9][10][11] Today, obesity is a worldwide public-health issue, with the rate of obesity increasing dramatically in the general population. According to data from the World Health Organization, 12 13% of adults aged 18 years and older (11% of men and 15% of women) are obese.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these well-established risk factors, additional risk factors suggested in the literature include non-White race/ethnicity (Berggren, Boggess, Funk, & Stuebe, 2012;Cheng et al, 2006;Colombara, Soh, Menacho, Schiff, & Reed, 2011;Dodd et al, 2012), shorter height (Cheng et al, 2013;Gupta et al, 2010;Mazouni et al, 2006;Parantainen et al, 2014), multiparity (Gupta et al, 2010;Mazouni et al, 2006;Øverland et al, 2012, lack of prenatal care (Sheiner et al, 2006), history of previous shoulder dystocia (Kleitman, Feldman, Walfisch, Toledano, & Sheiner, 2016;Øverland, Spydslaug, Nielsen, & Eskild, 2009), prolonged labor (Gupta et al, 2010;Øverland et al, 2012, and induction of labor (Dodd et al, 2012;Øverland et al, 2012).…”
mentioning
confidence: 99%
“…(2) Women who had episiotomy done before have a weaker scar tissue in this area which makes a preventive episiotomy more likely to be done to prevent perineal tears. (3) Women who give birth to higher birth weight infants, a known factor to make preventive episiotomy [14], tend to have heavier babies in the following pregnancies. (4) The pathophysiology of scar tissue created at the episiotomy site.…”
Section: Discussionmentioning
confidence: 99%